Effects of dietary myo-inositol on growth performance, hematological parameters, antioxidant capacity, immunity and resistance against Aeromonas hydrophila in red swamp crayfish (Procambarus clarkii) - Guoliang Ruan; Heng Zhang; Wei Chen; Liu Fang; Jiu Shu; Qian Wang (Aquaculture Reports)
The red swamp crayfish (Procambarus clarkii) is of importance in the crustacean farming of China. Myo-inositol (MI) as a vitamin-like nutrient has not been investigated in P. clarkii yet, current study was made to investigate the effect of dietary MI on the growth and health of the crayfish, P. clarkii (8.05 ± 0.71 g) fed with diets containing 0 (M0), 800 (M1), 1600 (M2), 2400 (M3), and 3200 (M4) mg/kg of MI for eight weeks. At the end of the feeding trials, all crayfish in MI-supplemented groups exhibited improved growth performance; the survival rate, weight gain, specific growth rate, and condition factor of M3 were significantly higher compared with the control, alongside with the highest digestive enzymes activities in M3 or M2 (P < 0.05). Dietary MI of M3 significantly decreased muscle’s crude lipid content, improved the hemolymph parameters (e.g., ALT and AST; the HDL-C/LDL-C ratio), antioxidative indices (MDA; T-AOC, T-SOD, CAT and GSH-Px), as well as promoted the expression of immune-related genes (gpxs, hsp70, ast and cypa) (P < 0.05). After 72 h of infection with Aeromonas hydrophila, the crayfish in M3 showed the highest survival among all the treatments, and higher AKP and LZM activities compared with the control (P < 0.05). Our results demonstrate that rational dietary MI can significantly enhance growth performance, digestive efficiency, antioxidant capacity and immunity, and disease resistance in P. clarkii, and 2.30–2.43 g/kg of dietary MI is recommended for this crayfish’s aquaculture.